Предмет: Математика,
автор: lolchek338
(a ^ 4 + a ^ - 4)/(a ^ 5 + a ^ - 3)
(2a ^ - 3 * a ^ - 5 * a ^ 7) ^ - 1
(a/3) ^ - 4 * (9/а ^ 2) ^ - 1 * (9/2a) ^ - 1
Ответы
Автор ответа:
0
Спрощені вирази будуть:
(a^4 * a^-4)/(a^5 * a^-3) = a^0/a^2 = 1/a^2
(2a^-3 * a^-5 * a^7)^-1 = 2^-1 * (a^-3 * a^-5 * a^7)^-1 = 2^-1 * a^-9 = 1/2a^9
(a/3)^-4 * (9/а^2)^-1 * (9/2a)^-1 = (3/a)^4 * (a^2/9) * (2a/9) = 2/27
Отже, спрощені вирази: 1/a^2, 1/2a^9 і 2/27.
Похожие вопросы
Предмет: Английский язык,
автор: lamalamaaaaaa1
Предмет: Алгебра,
автор: briktetana5
Предмет: Українська література,
автор: nastiapi
Предмет: Биология,
автор: bozumovaerkeajym